Proportional-integral based fuzzy sliding mode control of the milling head. (August 2016) - Zhao, Pengbing; Shi, Yaoyao; Huang, Jin
Abstract: A -axis (that is, the milling head) is an essential assembly in the five-axis CNC machine tools, positioning precision of which directly affects the machining accuracy and surface qualities of the processed parts. Considering the influence of nonlinear friction and uncertain cutting force on the control precision of the A -axis, a novel fuzzy sliding mode control (FSMC) based on the proportional-integral (PI) control is designed according to the parameters adaptation. Main idea of the control scheme is employing the fuzzy systems to approximate the unknown nonlinear functions and adopting the PI control to eliminate the input chattering. Simulation analyses and experimental results illustrate that the designed control strategy is robust to the uncertain load and the parameters perturbation. Graphical abstract: Highlights: The milling head with high-precision, high-torque and high-stiffness is proposed. Fuzzy sliding mode control based on the proportional-integral control is designed. The designed control strategy is verified by the simulations and experiments.